Marketing Strategy of Umroh and Hajj Savings Product at Syariah Peoples’s Credit Bank - Sabet, Fia Birtha Al (ProBisnis : Jurnal Manajemen, 2024)
Marketing strategy is a way for a company to achieve marketing goals. Marketing goals must clearly state how much market share and sales volume it wants to achieve and when it wants to be achieved. Thus, marketing strategy is the whole step to achieve a certain target. The marketing strategy analysis stage is an important stage of the strategy management process and is a critical step which is one of the indicators of the success of Islamic banking management which requires special precision to produce the right strategy and marketing choices. Like service products in other fields, banking products also require a marketing strategy to sell their products. There are many products offered by banks, especially Islamic banks. One of the Islamic banking institutions in the Bangil area, Pasuruan as a city of santri is Syariah Peoples’s Credit Bank (Bank Prenkreditan Rakyat Syariah), namely PT. Bank Penkreditan Rakyat Syariah (BPRS) Daya Artha Mentari. At PT. BPRS Daya Artha Mentari, the most superior product is the Umrah and Hajj savings product. However, this product has experienced fluctuations in its marketing. So this study will discuss the marketing strategy for Hajj and Umrah savings products at PT. BPRS Daya Artha Mentari. This research method uses a qualitative method. Based on the results of the study, it was found that the marketing strategy for Umrah and Hajj products at PT. BPRS Daya Artha Mentari is through a promotional strategy with the door to door method and sales with the cross selling method. Although using these strategies, there are still obstacles faced which are the cause of the decline in the number of product sales, namely the limited human resources who are qualified in product marketing and the views of the community who do not yet understand the concept and content of the Umrah and Hajj Savings program offered.